2018
DOI: 10.3390/nano8040197
|View full text |Cite
|
Sign up to set email alerts
|

Mobility Enhancement in Amorphous In-Ga-Zn-O Thin-Film Transistor by Induced Metallic in Nanoparticles and Cu Electrodes

Abstract: In this work, we fabricated a high-mobility amorphous indium-gallium-zinc-oxide (a-IGZO) thin-film transistor (TFT) based on alumina oxide (Al2O3) passivation layer (PVL) and copper (Cu) source/drain electrodes (S/D). The mechanism of the high mobility for a-IGZO TFT was proposed and experimentally demonstrated. The conductivity of the channel layer was significantly improved due to the formation of metallic In nanoparticles on the back channel during Al2O3 PVL sputtering. In addition, Ar atmosphere annealing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…The ALD growth step for the Al 2 O 3 gate insulator requires subjecting the already‐deposited IGZO layer to vacuum as well as chemical precursors which may change the properties of the surface. Most notably, this may result in the formation of indium nanoparticles and/or the adsorption of OH − at the surface of the semiconductor, with the net effect of increasing the conductivity of the IGZO layer at this interface. Inserting a barrier SiO 2 layer between IGZO and ALD Al 2 O 3 , for instance, may improve the device operation.…”
Section: Structural and Electrical Characteristics Of Source‐gated Trmentioning
confidence: 99%
“…The ALD growth step for the Al 2 O 3 gate insulator requires subjecting the already‐deposited IGZO layer to vacuum as well as chemical precursors which may change the properties of the surface. Most notably, this may result in the formation of indium nanoparticles and/or the adsorption of OH − at the surface of the semiconductor, with the net effect of increasing the conductivity of the IGZO layer at this interface. Inserting a barrier SiO 2 layer between IGZO and ALD Al 2 O 3 , for instance, may improve the device operation.…”
Section: Structural and Electrical Characteristics Of Source‐gated Trmentioning
confidence: 99%
“…On the other hand, with displays with high resolution (≥8 K), high frame-rate (≥480 Hz) and large size (≥110 inches) becoming increasingly popular, copper (Cu) is considered to be the most promising electrode material in TFTs due to its low resistivity, good thermal stability, high thermal conductivity and good electromigration reliability [ 14 , 15 ]. As the source and drain (S/D) electrodes have direct contact with the semiconductor layer, the contact characteristics between them are very important in the research of TFTs with Cu S/D electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…However, several reports have been revealed that the diffusion of Cu into IGZO deteriorates the electrical performance because it is acting as acceptor-like trap states of IGZO TFT [11]- [15]. Recently, a low resistance stacked structure of S/D on IGZO was introduced to enhance the contact properties [16]- [18]. The Ti and Mo has used widely as an interfacial layer to protect the Cu diffusion into IGZO and to reduce the impact of the Schottky barrier.…”
Section: Introductionmentioning
confidence: 99%